Integrating information literacy instruction (ILI) through resource-based school projects: An interpretive exploration - Yu, Halida; Noordin, Siti Arpah; Mokhtar, Sobariah Awang; Abrizah, Abdullah (IOS Press, 2010)
Resource-based school projects have good potential to be an effective approach in information literacy instruction (ILI). These projects offer the opportunity for students to engage in information problem-solving learning activities and employ various learning skills, including information literacy (IL). The researchers seek to explore ILI through resource-based projects to shed more light in this area. This paper aims at better understanding the integration of IL through the context of school project work. Adopting a qualitative research approach, the respondents involved in this single case study are three project supervisors/teachers and six 15 years old students who are involved in two project assignments. The study employed semi-structured interviews with the teachers and focus-group interview with the students. Findings of the study show that all teachers interpret IL as ICT skills and admitted to not teaching "IL" during project supervisions. It also reveals that only minimum IL integration took place during project supervision, where only IL elements of lower levels were involved in that integration. © 2010/2011 - IOS Press and the authors. All rights reserved.